2020
DOI: 10.1101/2020.04.16.20062141
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Impact of non-pharmaceutical interventions on documented cases of COVID-19

Abstract: Background: The novel coronavirus (SARS-CoV-2) has rapidly evolved into a global epidemic. To control its spread, countries have implemented non-pharmaceutical interventions (NPIs), such as school or border closures, while others have even enforced a complete lockdown. Here we study the effectiveness of NPIs in reducing documented cases of COVID-19. Methods: We empirically estimate the impact of NPIs on documented COVID-19 cases in a cross-country analysis. A Bayesian hierarchical model with a time-delayed eff… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
131
2
2

Year Published

2020
2020
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 97 publications
(147 citation statements)
references
References 30 publications
9
131
2
2
Order By: Relevance
“…Retrospective analyses of NPI impact on disease spread, to date, have primarily consisted of cross-country analyses or focused on outcomes in China. 2,20,21,[23][24][25] In one comparison of 20 countries, Banholzer et al found public venue closures to be the most effective NPI in reducing new cases, followed by public gathering bans, non-essential business closures, and international travel restrictions, with school closures decreasing case count minimally. Interestingly, they found 'lockdowns' to be among the least effective policies in mitigating disease spread.…”
Section: Context and Contributionmentioning
confidence: 99%
See 2 more Smart Citations
“…Retrospective analyses of NPI impact on disease spread, to date, have primarily consisted of cross-country analyses or focused on outcomes in China. 2,20,21,[23][24][25] In one comparison of 20 countries, Banholzer et al found public venue closures to be the most effective NPI in reducing new cases, followed by public gathering bans, non-essential business closures, and international travel restrictions, with school closures decreasing case count minimally. Interestingly, they found 'lockdowns' to be among the least effective policies in mitigating disease spread.…”
Section: Context and Contributionmentioning
confidence: 99%
“…Mandated policies including limitations on mass gatherings, business closures, and stay-at-home orders have aimed to encourage social distancing and flatten the curve. [2][3][4] As of April 30, 2020, over 3,249,000 COVID-19 cases have been confirmed worldwide, with more than 1,067,000 cases and 62,000 resulting deaths in the United States. 5 In an effort to contain the virus, broad shutdowns have resulted in severe economic impacts including 26 million Americans filing for unemployment within a 5 week period.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This reduction can mainly be explained by reduced number of contacts among people owing to movement restrictions. Studies on the impact of lockdown in other countries also reported reduction in reproductive number which translates in to flattening of the curve and delaying of peak (14)(15)(16)(17)(18)(19). Yet as mentioned earlier, the effective R0 estimations are dynamic and may change over age structure, time and nature of intervention.…”
mentioning
confidence: 94%
“…These studies yielded conflicting conclusions. Depending on data sources and epidemiological model design assumptions, some studies identified lockdown (stay at home order) as the most effective intervention 5,9 while others found little additional impact, if any, compared to other interventions 4,6,10 . Epidemiological studies of interventions against an epidemic face several challenges.…”
Section: Introductionmentioning
confidence: 99%